Apis mellifera and Melipona scutellaris exhibit differential sensitivity to thiamethoxam - Miotelo, Lucas [UNESP]; Mendes dos Reis, Ana Luiza [UNESP]; Malaquias, José Bruno [UNESP]; Malaspina, Osmar [UNESP]; Roat, Thaisa Cristina [UNESP] (Elsevier, 2021)
Apis mellifera is a pollinator insect model in pesticide risk assessment tests for bees. However, given the economic and ecological importance of stingless bees such as Melipona scutellaris in the Neotropical region, as well as the lack of studies on the effect of insecticides on these bees, toxicity tests for stingless bees should be carried out to understand whether insecticides affect both species of bees in the same manner. Thus, the present study quantified the differential sensitivity of the bees M. scutellaris and A. mellifera to the oral ingestion of the insecticide thiamethoxam by determining the mean lethal concentration (LC50), mean lethal time (LT50), and their effect on the insecticide target organ, the brain. The results showed that the stingless bee is more sensitive to the insecticide than A. mellifera, with a lower LC50 of 0.0543 ng active ingredient (a.i.)/μL for the stingless bee compared to 0.227 ng a.i./μL for A. mellifera. When exposed to a sublethal concentration, morphological and ultrastructural analyses were performed and evidenced a significant increase in spaces between nerve cells of both species. Thus, A. mellifera is not the most appropriate or unique model to determine the toxicity of insecticides to stingless bees.
Keywords: Model organism; Mushroom body; Neonicotinoid; Stingless bees; Toxicity tests; Ultrastructure